2011
DOI: 10.1002/stem.738
|View full text |Cite
|
Sign up to set email alerts
|

Human Gingiva-Derived Mesenchymal Stromal Cells Attenuate Contact Hypersensitivity via Prostaglandin E2-Dependent Mechanisms

Abstract: The immunomodulatory and anti-inflammatory functions of mesenchymal stromal cells (MSCs) have been demonstrated in several autoimmune/inflammatory disease models, but their contribution to the mitigation of contact hypersensitivity (CHS) remains unclear. Here, we report a new immunological approach using human gingiva-derived MSCs (GMSCs) to desensitize and suppress CHS and the underlying mechanisms. Our results showed that systemic infusion of GMSCs before the sensitization and challenge phase dramatically s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
152
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 145 publications
(161 citation statements)
references
References 60 publications
(130 reference statements)
9
152
0
Order By: Relevance
“…Similar immunomodulatory mechanisms mediated by elevated IDO have also been reported for other types of oral MSCs, particularly human periodontal ligament stem cells (Wada et al, 2009). Additionally, findings from both in vitro and in vivo studies have indicated that GMSCs could significantly inhibit Th17 cells and simultaneously promote the expansion of CD4 + CD25 + FoxP3 + regulatory T-cells (Tregs) (Zhang et al, 2009(Zhang et al, , 2010Su et al, 2011;Tang et al, 2011). However, further studies are needed to elucidate the underlying mechanisms of interplay between gingivaderived MSCs and specific types of T-helper cells.…”
Section: Effects Of Gmscs On T-cellsmentioning
confidence: 60%
See 4 more Smart Citations
“…Similar immunomodulatory mechanisms mediated by elevated IDO have also been reported for other types of oral MSCs, particularly human periodontal ligament stem cells (Wada et al, 2009). Additionally, findings from both in vitro and in vivo studies have indicated that GMSCs could significantly inhibit Th17 cells and simultaneously promote the expansion of CD4 + CD25 + FoxP3 + regulatory T-cells (Tregs) (Zhang et al, 2009(Zhang et al, , 2010Su et al, 2011;Tang et al, 2011). However, further studies are needed to elucidate the underlying mechanisms of interplay between gingivaderived MSCs and specific types of T-helper cells.…”
Section: Effects Of Gmscs On T-cellsmentioning
confidence: 60%
“…Similar to BMSCs (English and Mahon, 2011;Lee et al, 2011), GMSCs exhibit potent immunomodulatory effects on several types of innate immune cells, particularly dendritic cells (DCs), macrophages, and mast cells (Zhang et al, 2010;Su et al, 2011). (Galli et al, 2011).…”
Section: Effects Of Gmscs On Innate Immune Cellsmentioning
confidence: 99%
See 3 more Smart Citations